2013
DOI: 10.1002/cbic.201200681
|View full text |Cite
|
Sign up to set email alerts
|

The C‐Terminal Extended Serine Residue Is Absolutely Required in Nosiheptide Maturation

Abstract: Serine qua non: Substitution of the extended Ser13 in the core peptide of nosiheptide by analogous amino acids prevented enamide dealkylation of the terminal residue for nosiheptide maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…; Liu et al . ). Flavohaemoglobins, possess an N‐terminal globin domain (a three‐on‐three a‐helical fold) linked to a C‐terminal domain containing NAD(P)H‐binding and FAD‐binding sites (Vasudevan et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Liu et al . ). Flavohaemoglobins, possess an N‐terminal globin domain (a three‐on‐three a‐helical fold) linked to a C‐terminal domain containing NAD(P)H‐binding and FAD‐binding sites (Vasudevan et al .…”
Section: Resultsmentioning
confidence: 97%
“…One mutagenesis study has shown that substitution of Ser13 does not particularly affect the biosynthetic pathway except for preventing de-acylation to the C-terminal amide by NosA. 331 There has been more interest in optimizing nosiheptide production 332335 due to its use as a livestock growth promoter. 66, 67 …”
Section: Thiopeptidesmentioning
confidence: 99%
“…The biosynthetic gene cluster of nosiheptide was elucidated in 2009 (21). Several groups have focused on the biosynthesis of nosiheptide, and progress has subsequently been made (26)(27)(28)(29)(30)(31)(32)(33). However, these studies have been limited to only the late modification stage without the involvement of the leader peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the functions or roles of the leader peptide could certainly provide an insightful basis to reveal all of the biosynthetic steps in nosiheptide biosynthesis. In addition, based on the feasibility of genetic manipulation in S. actuosus ATCC 25421, exploration of the roles of the leader peptide in the biosynthetic gene cluster of nosiheptide has become approachable (21,27,28).…”
Section: Discussionmentioning
confidence: 99%